Perkuatan Beton Ringan Fiber Dengan Mengunakan Anyaman Bambu - Zuraidah, Safrin; Hastono, Budi; Juasman, Rikardus Exceliano (Universitas Dr. Soetomo, 2021)
Along with the rapid development of construction and infrastructure, so the need for concrete materials increases. In the field of engineering the development of concrete materials, from time to time, we always carry out innovations and research for construction materials. The price of steel reinforcement is increasingly expensive so it is very difficult for the middle to lower class to reach. The use of bamboo as a construction material has not proven its scientific quality and there is a lack of public understanding of the mechanical properties of bamboo. In order to provide an understanding and prove the quality of bamboo, this research was conducted by utilizing bamboo as reinforcement in lightweight fiber concrete. This research also uses strapping band type additives and the use of styrofoam as a substitute for coarse aggregate, the use of strapping band waste that is ± 70 mm long with a composition of 0%, 5%, 10%, and 15% of the weight of cement, styrofoam of 20% of the volume. test object. The method used is an experimental method that is carried out in a concrete laboratory.From the results of this study, the volume weight of concrete without woven bamboo was 16.67 kg / m³, decreased by (8.67%), and with woven bamboo was 15.22 kg / m³, compressive strength was 11.23 Mpa, decreased by (24.40%), and with bamboo plaited by 8.49 Mpa, split tensile strength of 1.65 Mpa, decreased by (3.03%), and with bamboo plaited by 1.6 Mpa, on 28 aged concrete days with a strapping band fiber content of 5%.It is recommended to use strapping band fibers of 5% of the weight of cement to obtain the optimum compressive strength and split tensile strength values, while the use of bamboo mat is not recommended for lightweight concrete.